Fractal nematic colloids - S. M. Hashemi (Nature Portfolio, 2017)
Topological defects in nematic liquid crystals can be controlled upon external stimuli for designing novel photonic materials. Here, Hashemiet al. show geometry-induced formation of fractal defects in nematic fluids with the fractal self-similarity more than 90% from micrometers to nanometres.